Is there an unexplored possibility to reduce tax evasion? Concentrating on moral and personality - Steinarsdóttir, Arna Laufey; Hermannsdóttir, Auður (Stofnun stjórnmála og stjórnsýslu, 2023)
The scope of tax evasion is significant in Iceland. By reducing such economic crime, it is possible to increase public income considerably. The aim of the study was twofold. Firstly, to shed light on what might explain why some members of society are more likely to evade taxes than others. In that regard, a focus was put on both tax morale and personality traits. Secondly, the study seeks to answer which groups of taxpayers should be targeted to reduce tax evasion. With an electronic convenience sample, responses were obtained from 593 individuals who answered a questionnaire measuring tax evasion, tax morale, and personality. The results revealed that tax morale has the strongest predictive value on whether people are likely to evade taxes. Furthermore, the personality traits of humility and honesty along with psychopathy are of considerable importance in this regard. The results of a cluster analysis showed that it is most optimal to divide taxpayers into three groups which were named the honorable citizens, the fickle citizens, and the cunning citizens. The honorable citizens are very unlikely to evade taxes and have high tax morale. It would therefore not be an efficient use of resources to focus on that group. The other two groups, the fickle and the cunning citizens, are groups that should be targeted. It is probably most feasible to prioritize strategies aimed at the fickle citizens, although the cunning citizens must also be considered. Different measures need to be used to target these groups, as is discussed in the paper. Umfang skattsvika er umtalsvert hér á landi. Sé dregið úr slíkum efnahagsglæpum er hægt að auka tekjur hins opinbera töluvert. Markmið rannsóknarinnar var annars vegar að varpa ljósi á hvað kunni að skýra það að sumir samfélagsþegnar eru líklegri en aðrir til að svíkja undan skatti. Í því skyni var bæði einblínt á skattasiðferði og persónuleikaeinkenni einstaklinga. Hins vegar var markmiðið að greina hvaða hópa skattgreiðenda sé fýsilegt að miða aðgerðir að með það að leiðarljósi að ...